Digital Flipbook-Based Mathematics Teaching Materials using RME Approach to Improve Mathematical Problem-Solving Ability - Mulyowati, Dwi; Fitriana, Laila; Triyanto, Triyanto; Wiraya, Ario (Jurnal Pendidikan Progresif, 2023)
Digital Flipbook-Based Mathematics Teaching Materials using RME Approach to Improve Mathematical Problem-Solving Ability. This research aims to determine the validity, practicality, and effectiveness of flipbook-based statistics teaching materials using realistic mathematics education (RME) approach in improving the mathematical problem-solving abilities of class XI AKL students at SMK N 1 Karanganyar. This research and development uses a 4D model. The assessment of the development of teaching materials is based on the validity and practicality aspects, while the assessment of mathematical problem-solving abilities is based on the effectiveness aspect. Data were collected through material expert and media expert validation sheets for validity aspects, teacher and student response questionnaires for practical elements, and experimental class and control class student answer sheets for effectiveness aspects. Material and media experts assessed the validity aspect, and experimental class students and teachers evaluated the practicality aspect. The effectiveness aspect was by looking at the average post-test score for the experimental and control classes via the t-test. The assessment results show that the teaching materials developed are valid, practical, and effective.  Keywords: teaching materials, realistic mathematics education, research and developmentDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202342